Recent Progresses on Remote Sensing Monitoring of Desertification - Di, Liping (Annals of Arid Zone, 2016)
Desertification is one of the serious environment problems faced by many countries in the world. It not only deteriorates the productivity of the fragile ecosystems but also causes serious environmental and social problems. Combating desertification has become the top priority for governments around the world, international organizations, and thc United Nations. Remote sensing is the only method of choice for monitoring desertification over large areas because of its capability of collecting data tiÂ·equently. synoptically, and objectively over such areas. Information derived from remote sensing data has been widely used in modeling and predication of desertification. It has also been used in supporting decision-making for combating desertification. This paper summarizes recent progresses on many aspects of remote sensing monitoring of desertification, including the availability of new remote sensing data and products for desertification research, desert mapping, dust storm monitoring, desertification monitoring, forces of desertification, and desertification modeling. It also presents the future directions in remote sensing of desertification.